Strategi Penghidupan Rumah Tangga di Das Garang Hulu - Yesy, Latifunnisa; Liesnoor, Setyowati Dewi (Geo-Image, 2019)
The research aim  to examine the livelihood strategies of houshold in the Garang Hulu watershed. The population in this research are 7.652 households which spreads in 4 villages there are Munding, Lerep, Kalirejo, and Pakintelan with 99 households as the sample. Area sampling and purposive sampling methods are used to decide which households near the river and to divide the research areas into two part there are  upstream area of DAS and downstream area of DAS. Data collection tools and techniques used were documentation, questioners, interviews, and observation. Data analysis techniques in this research used were quantitative descriptive and spatial analysis. The results showed that the intensification strategy in the upstream watershed was agroforesty while in the downstream watershed area was ‘panca usaha tani” strategy. The diversification strategy through livestock and trade was taken in the upstream area, while the downstream area was dominated by the service sector as the employees or workers. The migration strategy  permanen and “menglajo”with the reason of working in the upstream area, while migration with the reason of marriage in the downstream watershed area.